RECREATIONAL ACTIVITIES IN GREEN OPEN SPACES IN IMAM BONJOL PARK AND ADITYAWARMAN MUSEUM PARK IN PADANG CITY - Risda Hayati; Noril Milantara, S.Hut, M.Si, IPM; Susilastri Susilastri (Sylva Jurnal Ilmu-ilmu Kehutanan, 2025)
Imam Bonjol Green Open Space is an active park as a public Green Open Space which is currently managed by the Padang City Environment Agency in the field of parks. Adityawarman Museum Park is a private Green Open Space because it is part of the Urban Environment Park with an area of ± 2.5 Ha. These two Green Open Spaces became the object of research with the aim to see the recreational activities of residents in the Green Open Space of Imam Bonjol Park and Adityawarman Museum Park. The data collected in this research is divided into two groups, namely primary data and secondary data. Recreational activities in both Green Open Spaces look at the internal aspects of visitors obtained through questionnaire data to visitors who are using Green Open Spaces. The results of research on recreational activities in Taman Imam Bonjol Green Open Space as a recreational destination for residents are walking/jogging, cycling, sitting & chatting, playing, culinary, learning and enjoying nature. The dominant recreational activity in Imam Bonjol Park Green Open Space is enjoying nature with an index (99.33%) with very suitable criteria and the dominant recreational activity in the Green Open Space of Adityawarman Museum Park is sitting & chatting with an index (92.67%) with very suitable criteria.